2010
DOI: 10.1086/656743
|View full text |Cite
|
Sign up to set email alerts
|

Possible Role of Aerosol Transmission in a Hospital Outbreak of Influenza

Abstract: Our findings suggest a possible role of aerosol transmission of influenza in an acute ward setting. Source and engineering controls, such as avoiding aerosol generation and improving ventilation design, may warrant consideration to prevent nosocomial outbreaks.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
108
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 107 publications
(109 citation statements)
references
References 37 publications
1
108
0
Order By: Relevance
“…(11) Two air sampling studies have shown that respirable particles containing influenza virus RNA can be found throughout health care facilities, (12,13) and a recent hospital study suggested that small aerosol particles from an influenza patient were blown by an air purifier toward other patients in a hospital ward, leading to additional infections much farther away. (14) Thus, many questions remain as to the risk of exposure to diseases like influenza and the circumstances under which respiratory protection is needed.…”
Section: Introductionmentioning
confidence: 99%
“…(11) Two air sampling studies have shown that respirable particles containing influenza virus RNA can be found throughout health care facilities, (12,13) and a recent hospital study suggested that small aerosol particles from an influenza patient were blown by an air purifier toward other patients in a hospital ward, leading to additional infections much farther away. (14) Thus, many questions remain as to the risk of exposure to diseases like influenza and the circumstances under which respiratory protection is needed.…”
Section: Introductionmentioning
confidence: 99%
“…Wong and colleagues used a computational fluid dynamics model to study the spread of an influenza outbreak in a hospital setting [39]. Concentrations of hypothetical virus-laden particles from modelled air distributions correlated closely with locations of infected patients.…”
Section: Comparing Results With Established Factsmentioning
confidence: 99%
“…This could be done through a ventilation network model, such as CON-TAM, or one of the many commercially available building simulation tools or even modeling a ward zone within a CFD simulation to assess the likely spatial distribution of infectious material in a real situation. In the case of CFD approaches, steady-state airflow models without the movement of people have been shown to have reasonable correlation with infection cases seen in ward (Wong et al 2010) and building (Yu et al 2004) outbreaks.…”
Section: Zonal Modeling Approachmentioning
confidence: 97%